Interferon and interferon-stimulated genes in HBV treatment - Li, Qirong; Sun, Baozhen; Zhuo, Yue; Jiang, Ziping; Li, Rong; Lin, Chao; Jin, Ye; Gao, Yongjian; Wang, Dongxu (Frontiers in Immunology, 2022)
Human hepatitis B virus (HBV) is a small enveloped DNA virus with a complex life cycle. It is the causative agent of acute and chronic hepatitis. HBV can resist immune system responses and often causes persistent chronic infections. HBV is the leading cause of liver cancer and cirrhosis. Interferons (IFNs) are cytokines with antiviral, immunomodulatory, and antitumor properties. IFNs are glycoproteins with a strong antiviral activity that plays an important role in adaptive and innate immune responses. They are classified into three categories (type I, II, and III) based on the structure of their cell-surface receptors. As an effective drug for controlling chronic viral infections, Type I IFNs are approved to be clinically used for the treatment of HBV infection. The therapeutic effect of interferon will be enhanced when combined with other drugs. IFNs play a biological function by inducing the expression of hundreds of IFN-stimulated genes (ISGs) in the host cells, which are responsible for the inhibiting of HBV replication, transcription, and other important processes. Animal models of HBV, such as chimpanzees, are also important tools for studying IFN treatment and ISG regulation. In the present review, we summarized the recent progress in IFN-HBV treatment and focused on its mechanism through the interaction between HBV and ISGs.